2017
DOI: 10.1038/s41598-017-09144-x
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for TAGLN2 in Phagocytosis of Lipopolysaccharide-activated Macrophages

Abstract: Activated macrophages have a greater ability of phagocytosis against pathogens that is mediated by large-scale actin rearrangement. However, molecular machineries that conduct this task have not been fully identified. Here, we demonstrate an unanticipated role of TAGLN2, a 22-kDa actin-binding protein, in Toll-like receptor (TLR)-stimulated phagocytosis. TAGLN2 was greatly induced in macrophages in response to lipopolysaccharide (LPS), a ligand for TLR4, partly via the NF-κB pathway. TAGLN2-deficient macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 50 publications
(58 reference statements)
3
54
1
Order By: Relevance
“…Each isoform performs unique biological roles and is expressed in different biological conditions. For example, transgelin‐2, the only transgelin protein with an upstream promoter region containing a NF‐κB consensus motif, is largely induced by the NF‐κB pathway in macrophages, while the other two isoforms are not significantly influenced …”
Section: Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Each isoform performs unique biological roles and is expressed in different biological conditions. For example, transgelin‐2, the only transgelin protein with an upstream promoter region containing a NF‐κB consensus motif, is largely induced by the NF‐κB pathway in macrophages, while the other two isoforms are not significantly influenced …”
Section: Structurementioning
confidence: 99%
“…The property of transgelin‐2 allowing it to be intercalated into the each G‐actin can also influence the stability of F‐actins . In cells, this property may result in the augmentation of F‐actin contents at the distal‐supramolecular activation cluster (d‐SMAC) of the immunological synapse (IS) in T cells, localization at the filopodia of B cells during B–T conjugation, and ruffles and phagocytic cups in macrophages …”
Section: Biochemical Characteristics Of Transgelin‐2: Actin Binding mentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective, we utilized TAGLN2 as we found in a previous report that TAGLN2 increases F-actin contents through stabilization of F-actin in T cells during IS formation. 17 Recently, we also found that TAGLN2 is significantly upregulated in macrophages in response to lipopolysaccharide and enhances macrophage phagocytic function, 26 demonstrating that TAGLN2 plays an essential role in actin dynamics at the immunological or phagocytic synapses. In the present study, more strikingly, drastic down-regulation of TAGLN2 in T cells from severe E0771 tumor-bearing mice further emphasizes that TAGLN2 is an important actin regulator for cytotoxic T cell adhesion to tumor target cells.…”
Section: Discussionmentioning
confidence: 88%
“…Macrophages, the first-line host defense against pathogenic microorganisms, are activated by cytokines (e.g., TNF-α, IFN-γ, and IL-4) and bacterial virulence factors (Mitchell et al, 2016;Salim et al, 2016). Activated macrophages trigger the activation of immunity-related signalling pathways, leading to the elimination of pathogenic bacteria (Kim et al, 2017). Previous studies have shown the clearance of almost 90% of invading Brucella by macrophages, but the remaining 10% can establish a safe niche for growth and reproduction in the endoplasmic reticulum (Von et al, 2012).…”
Section: Discussionmentioning
confidence: 99%